Users’ Motivation and Attitude Towards Print Media Among College Students in Kerala : Implications for the Design of Dissemination Strategies - Saji, T. G. (Indian Journal of Marketing, 2018)
Conducting a survey with 352 students pursuing higher education in Arts and Science colleges in Kerala, under a multivariate statistical framework, this research investigated the users’ motivations and value importance to the reported news from the readers’ perspectives in Kerala. The study employed multi - dimensional scaling (MDS) technique to segment the newspaper market according to the perceived similarities in the respondents’ motivations, and the findings offer evidence for the presence of diverging motives among young readers in the State. Multiple discriminant analysis administered in the research was able to make out the perceptual differences of readers based on their newspaper choices. The findings suggested the presence of two dimensions of discrimination among the newspaper brands - language simplicity and news credibility on one side and political bias and coverage of news on the other end. Language simplicity along with political reasons separated Malayalam newspaper brands from the leading English dailies, while the latter were favored in terms of the quality of news contents. In sum, youth in Kerala was inclined to adopt a utilitarian approach towards newspaper reading. Hence, the newspaper brands should be more familiar with the perceptual differences among the readers on a wider and richer perspective based on which they should design dissemination strategies to expand their business frontiers.